Association of Mother's Knowledge about Toddler Stimulation with Children's Development in Posyandu District Letung - Febrina, Trisya Yona; Natalia, Regina; Badar, Mawardi (Future Science, 2024)
Developmental problems that occur in toddlers are caused by the lack of stimulation given to them. This condition occurs due to a lack of parental knowledge about stimulation that is appropriate for the age of toddlers. This study aims to determine the relationship between maternal knowledge about the stimulation of toddler development and child development at Posyandu Cempaka Letung Village in 2023. We conducted a cross-sectional study of 60 mothers and toddlers. They were recruited through a total sampling technique with the criteria of mothers who have toddler children, mothers who are willing to be respondents, and mothers who can read and write. Furthermore, the data will be analyzed using Somers'd test. The results of this study showed that there was a significant relationship between mothers' knowledge about stimulation and toddler development (P-value 0.004, gamma 0.842). This study confirms the relationship between mothers' knowledge about stimulation of toddler development and child development at Posyandu Cempaka, Letung Village in 2023. We suggest that it is important to improve mothers' knowledge of toddler development.